Urbanization and its Impact on Land Use and Land Cover in Al Buraimi City, Oman Using Remote Sensing and GIS - Ansari Tauseef Ahmad Ahmad; Singh Chandan Kumar; Albawwab Wael (Journal of Landscape Ecology)
Rapid urbanization poses significant challenges that can transform the physical and socio-economic environment of a city. Oman, a coastal country, has experienced a rapid increase in urbanization over the past decades. As statistical data show, the population increased significantly from 1955 to 2023, ranging from 2.5 % to 88 %. Similarly, the population in Al Buraimi Governorate has doubled since 1993, with an estimated population of 121,802 (NCSI, 2021) Al Buraimi City facing significant challenges. The city’s rapid growth in population burdening its infrastructure, traffic, municipal, education and public health capacity. This paper investigates the transformation of Land Use (LU) / Land Cover (LC) change from 2003 to 2023 in relation to population growth, employing both spatial and non-spatial methods to analyze the urban sprawl. The study focuses on the four main objectives: 1. To identify distinct types of sprawls (e.g., continuous, leapfrog, ribbon) and their spatial distribution proximity areas. 2. To examine the factors driving urban sprawl, including population growth, industrial development, socio-economic and educational opportunities. 3. To assess LU/LC changes over the study period using geospatial methods. 4. To forecast urban sprawl pattern using statistical models, providing insights into potential future developments. Given the limited understanding of urban sprawl in the study area, this research aims to address the complex challenges of urbanization and recommends sustainable resource development strategies. The results show that between 2003 to 2023, built-up areas increase from 13.14 % to 14.88 %, roads and other areas from 9.92 % to 11.23 % and vegetation cover decline from 3.93 % to 3.37%. Population, road and built-up area densities show significant increase. The population density rose from 27.72 % to 44.12 %, road density surged from 13.86 % to 47.04 %, built-up area density grew from 25.68 % to 41.92 %. Depending on the forecast results of urban sprawl, the low sprawl (45 %-55 %) with higher density and less probability, medium sprawl (55 %-65 %) with moderate expansion probability, high sprawl (65 %-75 %) with increased probability of expansion and very high sprawl (> 75 %) with lower density, high probability of expansion. The areas with a high population, road or built-up area density are less likely to sprawl in the city of Al Burami. Additionally, three sprawl patterns, continuous, leapfrog and ribbon pattern in the study area were identified, helping in further solutions to urbanization.